The Shariah Advisory Council in the Malaysian Islamic financial institutions: features and legal issues - Md Dahlan, Nuarrual Hilal; Abdul Jalil, Ahmad Zafarullah; Zainol, Zairani; Maamor, Selamah (Inderscience Publishers, 2016)
The Malaysian Shariah Advisory Council ('SAC'), established under the Central Bank of Malaysia Act 2009 (Act 701), acts as an authority for the ascertainment of Islamic law in the operation of Islamic Financial Institutions ('IFIs').Its decision is binding on all IFIs, the Bank Negara Malaysia, the Shariah Committee, the court of law and the arbitrators in Malaysia. Nonetheless, this power may be abused by the SAC to the detriment of the customer stakeholders as the SAC is immune from any legal action.This paper aims to examine the features and legal issues of the SAC.The examination uses legal research methodology.This paper finds that the immunity conferred on the SAC should be abolished and be subject to the judicial scrutiny for the benefits of the IFIs' development in Malaysia.At the ending part of this paper, the authors provide certain recommendations in regard to the issues discussed.